Techno-Economic Analysis of Floating Solar PV on Reservoir Ash Pond in Coal-Fired Power Plants - Warto; Tobing, Sheila (International Journal of Education, Science, Technology, and Engineering (IJESTE), 2024)
The increasing global energy demand drives the development of efficient and sustainable renewable energy solutions. Floating Solar PV (FSPV) technology offers a viable solution by utilizing water surfaces such as reservoir ash ponds in coal-fired power plants without requiring additional land. This study aims to analyze the technical and economic aspects of an FSPV system with a capacity of 15.2 kWp using HelioScope and Homer Pro software, assuming Global Horizontal Irradiance (GHI) data from the National Solar Radiation Database. The analysis methods include annual energy production, Net Present Cost (NPC), Levelized Cost of Energy (LCOE), and other economic metrics such as Return on Investment (ROI), Internal Rate of Return (IRR), and Simple Payback Period for various grid electricity price escalation scenarios. The results show that a 5% annual increase in grid electricity prices reduces the simple payback period from 18.2 years to 13 years, with an ROI increase to 6.3% and an IRR of 7.1%. This study concludes that the FSPV system not only supports the transition to clean energy but also offers greater financial benefits under scenarios of rising grid electricity prices.